Social Exclusion and the Hierarchical Defense System Comment on MacDonald and Leary (2005). [article]. - Corr, Philip J.
G. MacDonald and M. R. Leary (2005) hypothesized that physical pain and social exclusion share many affective features in common. In this comment, the author discusses the implications of J. A. Gray and N. Mc Naughton's (2000) hierarchical defense system model which, MacDonald and Leary used in the development of their theoretical claims. Issues are discussed that require at least, clarifications, but more substantive problems need closer considerations of hierarchically organized . It is argued that research findings may be better understood (a) by systems of interacting neural modules, which lead state dissociations between affective states , and (b) by general modulatory influences on the entire defense system that lead to trait associations (i. e., personality) between physical pain and emotional distress. -- ( from the author).
Keywords: Psychology-Periodicals.